(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Replica clothing as worn by Robert F. Scott and Roald Amundsen in their race to be the first on the South Pole and by George Mallory in his ascent of Everest was tested for thermal insulative properties. These were benchmarked against modern day explorer clothing. Results are discussed in terms of insulation, insulation per weight, and wind protection. Further the effects of clothing on energy consumption were considered as well as the effect of altitude on insulation and energy consumption. The biggest advantage of modern clothing seems to be its lower weight. Scott's clothing resulted in extra energy usage for the wearers and provided less insulation than Amundsen's, though sufficient while active. The Mallory clothing had a low energy requirement due to the incorporation of ‘slippery’ silk layers. Its insulation would have been sufficient down to -30 °C in low wind. If wind were to increase, the clothing would however not have provided the required insulation.